Evaluation of the Effect of Chlorhexidine Mouthwash on Blood Pressure: A Narrative Literature Review - Yonezaki, Mayara; Almeida, Pollyanna; de Oliveira, Eduarda; Ramos, Giovanna; Bezerra, Giovanna; da Silva, Marcos Vinícius; Moutinho, Raphael; Moreira, Cláudia Lúcia; Cruz, Adriana (Scientific Letters, 2025)
This article presents a narrative review investigating the use of chlorhexidine mouthwash and its impact on blood pressure and cardiovascular health. Chlorhexidine, a widely used antimicrobial in Dentistry, has been associated with risks, such as increased blood pressure. The bibliographic research included articles published between 2014 and 2024, using the PubMed, SciELO, and the Virtual Library of the Ministry of Health databases, with keywords including “chlorhexidine”, “mouthrinse”, “mouthwash”, “nitrate” and “blood pressure”. The results indicate that chlorhexidine may disrupt nitric oxide homeostasis, essential for blood pressure regulation, by inhibiting oral microbiota bacteria that reduce nitrate to nitrite. Although effective in reducing pathogenic microorganisms, chlorhexidine should be prescribed with caution, considering its potential hypertensive effects. The study concludes that further research is needed regarding the contexts of chlorhexidine use and prescription, as well as the development of oral hygiene protocols that balance the elimination of pathogenic microorganisms with the preservation of beneficial microbiota.